(untitled) (Altre Modernità, 2019)
The article aims at rereading Giulio Piccini’s (alias Jarro) literary works by identifying the international models that underlie his production. Unduly defined as the mysterious pioneer of Italian detective fiction, Piccini actually moulds his novels on Gaboriau’s, Féval’s and especially Boisgobey’s production. La Vieillesse de Monsieur Lecoq is presented as the main model for Piccini’s most popular detective novel, I ladri di cadaveri: an actual repertoire of themes and sequences through which Piccini shapes the first, serial detective novels in Italian literature.